A solid oxide battery with a catalytically active isolation layer and its preparation method and application
By introducing a catalytically active isolation layer into the electrolyte support structure of the solid oxide battery, the problems of obstructed oxygen ion transfer and difficulty in densification of the isolation layer are solved, and the battery performance and cost reduction are improved.
Patent Information
- Application Number
- CN202411809517.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-06
- Filing Date
- 2024-12-10
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-10
Smart Images

Figure CN119297352B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide batteries, and more specifically, to a solid oxide battery having a catalytically active isolation layer, and a preparation method and application thereof. Background Art
[0002] Solid oxide batteries with ion conductor oxides as electrolytes can convert electrical energy into chemical energy by electrolyzing water and carbon dioxide, or convert the chemical energy of hydrogen and carbon-based fuels into electrical energy. They are usually used in new chemical energy storage, distributed power generation, and grid "peak shaving and valley filling". Among them, the carbon dioxide conversion efficiency of solid oxide electrolysis cells is relatively high, which has great advantages over other electrolysis technologies.
[0003] Improving the power generation efficiency of fuel cells and the conversion efficiency of electrolytic cells, reducing the cost of battery manufacturing and extending the service life of batteries are the keys to promoting the industrialization of solid oxide batteries. Nickel-based electrode supports and are currently the two most common solid oxide battery structures. Nickel-based electrode supported batteries generally use Ni-YSZ fuel electrodes as the battery support layer, while the electrolyte layer is very thin (10-50 microns), and usually exhibit higher battery performance. However, the reaction site of the Ni-YSZ electrode is limited to the three-phase interface of gas (reactant)-electronic conductor (Ni)-ion conductor (YSZ). Ni is prone to carbon deposition or poisoning, resulting in electrode inactivation and reducing battery service life. Metal oxides with ion-electron mixed conductivity can exhibit high activity, resistance to carbon deposition and resistance to poisoning through component structure design optimization, and can be used as advanced battery electrodes. Metal oxide electrodes are generally more suitable for electrolyte-supported batteries.
[0004] In addition to good compatibility with electrodes, electrolyte-supported batteries have a simple structure and a relatively easy manufacturing process. However, since the electrolyte needs to serve as a supporting layer, its thickness is required to be in the hundreds of microns, which hinders the transfer of oxygen ions. In addition, an isolation layer needs to be introduced to prevent the oxide electrode and electrolyte from reacting during the preparation process. A non-densified isolation layer will further hinder the oxygen ion transfer process, and an overly dense isolation layer will have difficulty in good contact with the porous electrode layer. Therefore, the performance of electrolyte-supported batteries is usually not as good as that of electrode-supported batteries.
[0005] The present invention designs an isolation layer with good catalytic activity, and based on this, develops a high-performance electrolyte-supported battery that is compatible with highly active electrode materials and has performance comparable to that of electrode-supported batteries. During the manufacturing process, the isolation layer activation process replaces the traditional isolation layer densification process, showing the advantages of high battery performance, low preparation cost and long operating life. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a solid oxide battery having a catalytically active isolation layer, and a preparation method and application thereof. In view of the problems of obstructed oxygen ion transfer in electrolyte-supported batteries and difficulty in densification of the isolation layer, the present invention introduces catalytically active substances into the porous isolation layer, so that the isolation layer blocks the generation of inert substances at the electrode / electrolyte interface while catalyzing the fuel electrode reaction and the oxygen electrode reaction. The catalytic isolation layer eliminates the problem of oxygen ion transfer difficulties in the porous isolation layer that restricts the battery process, and significantly improves battery performance.
[0007] A first aspect of the present invention provides a solid oxide battery.
[0008] A solid oxide battery with a catalytically active isolation layer, characterized in that it comprises a fuel electrode, a first catalytic isolation layer, an electrolyte, a second catalytic isolation layer, and an oxygen electrode stacked in sequence; the fuel electrode is a perovskite-type La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3; the electrolyte is YSZ; the oxygen electrode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3; the catalytic isolation layer includes a cerium oxide-based ion conductor and a catalyst.
[0009] In the solid oxide battery provided by the present invention, the catalytic isolation layer has three main functions: function one is to inhibit the generation of inert phase at the electrode / electrolyte interface during battery preparation; function two is to allow oxygen ions in the battery reaction to pass through the isolation layer to complete the transfer between the electrode and the electrolyte; function three is to catalyze the electrode reaction. The introduction of the catalyst solves the problem that the battery performance is limited by the inefficient transfer of oxygen ions in the porous isolation layer.
[0010] Preferably, the cerium oxide-based ion conductor in the isolation layer is Ce 0.9 G 0.1 O 1.95 .
[0011] Preferably, the catalyst in the isolation layer is Ce 0.95 Co 0.05 O3.
[0012] Preferably, the thickness of the first isolation layer is 3-20 μm, and / or the thickness of the second isolation layer is 3-20 μm.
[0013] Preferably, the YSZ electrolyte is 8 mol % Y2O3 stabilized ZrO2, referred to as 8YSZ.
[0014] Preferably, the thickness of the 8YSZ electrolyte is 200-1200 μm.
[0015] Further preferably, the thickness of the 8YSZ electrolyte is 250-500 μm.
[0016] Preferably, the La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 The thickness of the O3 electrode is 40-80 μm.
[0017] More preferably, the La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 The thickness of the O3 electrode is 50-70 μm.
[0018] Preferably, the La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The thickness of the O3 electrode is 40-80 μm.
[0019] More preferably, the La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The thickness of the O3 electrode is 50-70 μm.
[0020] A second aspect of the present invention provides a method for preparing a solid oxide battery having a catalytically active isolation layer.
[0021] A method for preparing a solid oxide battery having a catalytically active isolation layer, characterized in that it comprises the following steps:
[0022] (1) preparing a cerium oxide-based ion conductor powder into a slurry, printing it on both sides of a YSZ electrolyte substrate, and performing a first calcination to obtain a first isolation layer and a second isolation layer having a porous structure;
[0023] (2) preparing a catalyst precursor into a solution and impregnating the solution into the pores of the isolation layer, followed by a second calcination to convert the precursor into a nanocatalyst in the pores of the isolation layer, thereby obtaining a first catalytic isolation layer and a second catalytic isolation layer;
[0024] (3) La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 powder and La 0.6 Sr 0.4 Co 0.2 Fe 0.8O3 powder is prepared into fuel electrode slurry and oxygen electrode slurry, and printed on the surface of the first isolation layer and the surface of the second isolation layer, followed by a third calcination to simultaneously produce the fuel electrode and the oxygen electrode, thereby ensuring the stability of the nanocatalyst structure and components in the isolation layer, and finally obtaining a solid oxide battery with catalytic activity in the isolation layer.
[0025] Preferably, in step (1), the cerium oxide-based ion conductor powder and the screen printing adhesive are mixed evenly to prepare a cerium oxide-based ion conductor powder slurry.
[0026] Preferably, the cerium oxide-based ion conductor powder is Ce 0.9 G 0.1 O 1.95 Powder, particle size is 10-25μm.
[0027] Preferably, Ce 0.9 G 0.1 O 1.95 The mass ratio of powder to screen printing adhesive is 1:1.
[0028] Preferably, in step (1), the temperature of the first calcination is 500-1000° C., and / or the time of the first calcination is 0.5-5 h.
[0029] Further preferably, in step (1), the temperature of the first calcination is 600-800° C., and / or the time of the first calcination is 1.5-2.5 h.
[0030] Preferably, in step (2), after the catalyst precursors are mixed, a certain amount of deionized water is poured into the mixture, and the mixture is stirred at 300-600 r / min at 50-80° C. After the mixture is completely dissolved, the mixture is allowed to stand at 20-30° C. to prepare a catalyst precursor solution.
[0031] Preferably, the concentration of the catalyst precursor solution is 0.5-5 mol / L.
[0032] Preferably, in step (2), the immersion time of the first isolation layer and the second isolation layer is 24-48 hours.
[0033] Further preferably, the impregnation process is carried out under negative pressure.
[0034] Preferably, in step (2), the temperature of the second calcination is 500-1000° C., and / or the time of the second calcination is 0.5-5 h.
[0035] Further preferably, in step (2), the temperature of the second calcination is 600-800° C., and / or the time of the second calcination is 1.5-2.5 h.
[0036] Preferably, in step (3), La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 powder and screen printing glue are mixed evenly to prepare La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 slurry.
[0037] Preferably, the La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 The particle size of O3 powder is 10-40μm.
[0038] Preferably, La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 The mass ratio of O3 powder and screen printing adhesive is 1:1.
[0039] Preferably, in step (3), La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 powder and screen printing glue are mixed evenly to prepare La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 slurry.
[0040] Preferably, the La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The particle size of O3 powder is 10-25μm.
[0041] Preferably, La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The mass ratio of O3 powder and screen printing adhesive is 1:1.
[0042] Preferably, in step (3), the temperature of the third calcination is 900-1200° C., and / or the time of the second calcination is 0.5-5 h.
[0043] Further preferably, in step (3), the temperature of the third calcination is 900-1000° C., and / or the time of the second calcination is 1.5-2.5 h.
[0044] Preferably, in step (3), the La 0.6 Ca 0.4 Fe0.9 Ru 0.1 La in O3 slurry 0.6 Ca 0.4 Fe 0.9 Ru 0.1 The mass percentage of O3 slurry powder is 25-70%.
[0045] Preferably, in step (3), the La 0.6 Sr 0.4 Co 0.2 Fe 0.8 La in O3 slurry 0.6 Sr 0.4 Co 0.2 Fe 0.8 The mass percentage of O3 slurry powder is 30-60%.
[0046] Preferably, the La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 powder was synthesized by solid phase synthesis method.
[0047] More preferably, the La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 powder synthesis includes the following steps:
[0048] La2O3, CaCO3, Fe2O3 and RuO2 powders were mixed by La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 The metal ions in O3 are mixed in a molar ratio, anhydrous ethanol and a surfactant are added, and the mixture is ball-milled into a slurry. After the slurry is dried, it is calcined at a high temperature and crushed to obtain a powder, thereby obtaining the metal oxide solid solution electrode powder.
[0049] Preferably, the rotation speed of the ball mill is 300-600 r / min, and / or the time of the ball mill is 12-36 h.
[0050] Preferably, the drying temperature is 60-80° C., and / or the drying time is 24-48 hours.
[0051] Preferably, the temperature of the high-temperature calcination is 900-1200° C., and / or the time of the high-temperature calcination is 10-20 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a scanning electron microscope image of the solid oxide battery of Example 1 of the present invention;
[0053] Figure 2 A schematic diagram of the structure of a solid oxide battery according to Example 1 of the present invention and a scanning electron microscope image of a catalytic isolation layer;
[0054] Figure 3 This is a performance diagram of a fuel cell in a hydrogen atmosphere according to Example 1 of the present invention;
[0055] Figure 4 This is a performance diagram of the electrolytic cell in a carbon dioxide atmosphere according to Example 1 of the present invention;
[0056] Figure 5 In Example 1 of the present invention, in a hydrogen-carbon dioxide mixed gas, 575-825 o Battery performance diagram of C;
[0057] Figure 6 For Example 1 of the present invention, at 750 o C. Battery performance diagram of mixed gas with different components;
[0058] Figure 7 In the embodiment 1 of the present invention, the voltage is 1.6V, 750 o C, long-term operation stability diagram of 80%H2-20%CO2 atmosphere;
[0059] Figure 8 This is a performance diagram of a fuel cell in a hydrogen atmosphere according to Example 2 of the present invention;
[0060] Fig. 9 In Example 2 of the present invention, in a hydrogen-carbon dioxide mixture, 575-825 o Battery performance diagram of C;
[0061] Fig.10 This is a fuel cell performance diagram of Comparative Example 1 in a hydrogen atmosphere;
[0062] Fig.11 For Comparative Example 1, in a hydrogen-carbon dioxide mixture, 575-825 o Battery performance diagram of C;
[0063] Fig.12 This is a fuel cell performance diagram of Comparative Example 2 in a hydrogen atmosphere;
[0064] Fig.13 For comparative example 2, in a hydrogen-carbon dioxide mixture, 575-825 o Battery performance diagram of C;
[0065] Fig.14 This is a fuel cell performance diagram of Comparative Example 3 in a hydrogen atmosphere;
[0066] Fig.15 For comparative example 3, in a hydrogen-carbon dioxide mixture, 575-825o Battery performance diagram of C;
[0067] Fig.16 This is a fuel cell performance diagram of Comparative Example 4 in a hydrogen atmosphere;
[0068] Fig.17 For comparative example 4, in a hydrogen-carbon dioxide mixture, 575-825 o Battery performance diagram of C;
[0069] Fig.18 This is a comparison chart of the maximum power density of Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 as hydrogen fuel cells;
[0070] Fig.19 It is a comparison chart of the battery performance of Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 in a hydrogen-carbon dioxide mixture. DETAILED DESCRIPTION
[0071] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0072] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0073] Example 1
[0074] This embodiment provides a solid oxide battery with a catalytically active isolation layer, which comprises an oxygen electrode (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3, referred to as LSCF), a first isolation layer with a thickness of 10μm (GDC@CDC), an electrolyte with a thickness of 250μm (YSZ), a second isolation layer with a thickness of 10μm (GDC@CDC), a fuel electrode with a thickness of 60μm (La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3, referred to as LCFR).
[0075] A method for preparing a solid oxide battery having a catalytically active isolation layer comprises the following steps:
[0076] (1) Preparation of LCFR fuel electrode powder by solid phase synthesis: According to La 0.6 Ca 0.4 Fe 0.9 Ru0.1 The corresponding precursor powders (La2O3, CaCO3, Fe2O3, RuO2) are weighed and placed in a ball mill, and ball milling beads and an appropriate amount of ethanol of the same mass as the powder are added, and the mixture is ball-milled at a speed of 300r / min for 12 hours until it is uniform to obtain a mixed slurry; the mixed slurry is dried at 60°C for 24 hours to form a mixed powder, and then calcined at 1000°C for 10 hours; a block is formed, broken into powder, and ball milling beads and an appropriate amount of ethanol of the same mass as the powder raw materials are added and placed in a ball mill, and then ball-milled, dried and calcined again. After the above steps, LCFR electrode powder with a particle size of 20-60μm is synthesized;
[0077] (2) Preparation of GDC isolation layer slurry: ethyl cellulose and pine alcohol were mixed, heated in a water bath at 50°C, stirred at 300 r / min, and allowed to stand at 25°C after complete dissolution to obtain a screen printing adhesive with a mass percentage of ethyl cellulose of 6%; GDC with a particle size of 10 μm and battery glue were mixed in a weight ratio of 1:1 to obtain GDC slurry (isolation layer slurry); the mass fraction of cerium oxide in the GDC slurry was 65%;
[0078] (3) Preparing LSCF oxygen electrode slurry: mixing LSCF electrode powder and screen printing glue in a weight ratio of 1:1 to obtain LSCF oxygen electrode slurry;
[0079] (4) Preparing LCFR fuel electrode slurry: mixing LCFR electrode powder and screen printing glue in a weight ratio of 1:1 to obtain LCFR fuel electrode slurry;
[0080] (5) Preparation of catalyst impregnation solution: According to Ce 0.9 Co 0.1 O 2-x The corresponding precursors (cerium nitrate CeN3O9·6H2O, cobalt acetate (CH3COO)2Co) were weighed and dissolved in an appropriate amount of deionized water to obtain a catalyst impregnation solution with a concentration of 1 mol / L.
[0081] (6) Preparation of solid oxide battery with catalytically active isolation layer: A 250 μm thick 8YSZ substrate was used as the electrolyte. GDC slurry was printed on both sides of the electrolyte. The electrolyte was then calcined at 800 °C for 2 h to form 10 μm thick GDC isolation layers (first isolation layer and second isolation layer) on both sides of the substrate. The substrate was then immersed in the catalyst impregnation solution for 24 h and then calcined at 800 °C for 2 h. oC was calcined for 2 hours to obtain a catalytic isolation layer GDC@CDC; LSCF electrode slurry and LCFR electrode slurry were printed on the surfaces of the first isolation layer and the second isolation layer respectively, and then calcined at 1050℃ for 2 hours to prepare LSCF oxygen electrode and LCFR fuel electrode with a thickness of 60μm on both sides respectively to obtain LSCF / GDC@CDC / YSZ / GDC@CDC / LCFR solid oxide battery.
[0082] The cross-sectional morphology of the solid oxide battery with catalytic activity of the isolation layer prepared above (characterized by scanning electron microscopy) is as follows Figure 1 As shown in the figure, it can be clearly seen that the LSCF oxygen electrode layer, LCFR fuel electrode layer and GDC separator layer all maintain a good porous structure. In addition, the LSCF oxygen electrode layer and LCFR fuel electrode layer are closely connected to the GDC separator layer on the corresponding side, and the GDC separator layer is also closely connected to the YSZ electrolyte layer. Figure 2 (a) and Figure 2 (b) Schematic diagrams of the structures of two types of batteries: one with an isolation layer not impregnated with catalyst and the other with an isolation layer impregnated with catalyst. Figure 2 (c) and Figure 2 (d) The morphology of the catalyst isolation layer without impregnation and the catalyst isolation layer with impregnation, respectively. It can be seen that the GDC isolation layer maintains a porous structure, while the CDC catalyst is attached to the GDC pores. The isolation layer not only prevents the electrolyte and electrode reactions, but also catalyzes the electrode process. Example 2
[0083] This embodiment provides a solid oxide battery having a catalytically active isolation layer. Different from the embodiment 1, the concentration of the catalyst impregnation solution in the embodiment 2 is 0.1 mol / L. Figure 8 and Fig. 9 The battery performance of Example 2 under different conditions is shown.
[0084] Comparative Example 1
[0085] This comparative example provides a solid oxide battery, which is different from Example 1 in that the Ce 0.9 Co 0.1 O 2-x Ce 0.9 G 0.1 O 1.95 The isolation layer (GDC@CDC) was replaced by unimpregnated Ce 0.9 G 0.1 O 1.95 Isolation layer. Fig.10 and Fig.11 The battery performance of Comparative Example 1 under different conditions is shown.
[0086] The performance of Comparative Example 1 in the fuel cell mode and the electrolytic cell mode are significantly lower than those of Example 1, indicating that the catalytically active isolation layer can significantly improve the performance of the solid oxide cell with an electrolyte support structure under different operating conditions.
[0087] Comparative Example 2
[0088] This comparative example provides a solid oxide battery, which is different from Example 1 in that the catalyst solution is replaced by a cobalt sintering aid solution. Fig.12 and Fig.13 The battery performance of Comparative Example 2 under different conditions is shown.
[0089] Compared with Example 1, the cobalt sintering aid has no obvious improvement on the battery performance, indicating that the use of the sintering aid to increase the density of the isolation layer has limited improvement on the battery performance. It also shows that the cobalt element in the isolation layer of Example 1 mainly improves the battery performance through catalysis rather than sintering aid.
[0090] Comparative Example 3
[0091] This comparative example provides a solid oxide cell, which differs from Example 1 in that only the second separator (located between the LCFR fuel electrode and the YSZ electrolyte) is impregnated with the CDC catalyst. Fig.14 and Fig.15 The battery performance of Comparative Example 3 under different conditions is shown.
[0092] Compared with Example 1, the catalyst in the fuel electrode end separation layer can significantly improve the performance of the battery, but the effect is not as good as adding catalysts to both the fuel electrode end separation layer and the oxygen electrode end separation layer.
[0093] Comparative Example 4
[0094] This comparative example provides a solid oxide cell, which is different from Example 1 in that only the first separator (located between the LSCF oxygen electrode and the YSZ electrolyte) is impregnated with the CDC catalyst. Fig.16 and Fig.17 The battery performance of Comparative Example 3 under different conditions is shown.
[0095] Compared with Example 1, the catalyst in the oxygen electrode isolation layer can improve the performance of the battery, but the effect is not as good as the catalyst in the fuel electrode isolation layer, nor as good as adding catalyst to both the fuel electrode isolation layer and the oxygen electrode isolation layer.
[0096] Product effect testing
[0097] Example 1: Hydrogen is introduced into the fuel electrode and air is introduced into the oxygen electrode. Example 1 is used as a fuel cell to generate electricity. The performance is as follows: Figure 3 As shown. Between 575 and 825 oThe maximum power density (P) of C is shown in Table 1 below:
[0098]
[0099] From the above test results, it is known that the solid oxide cell with catalytic activity in the isolation layer exhibits good fuel cell performance in a pure hydrogen atmosphere.
[0100] Test Example 2
[0101] Example 1: Carbon dioxide is introduced into the fuel electrode and air is introduced into the oxygen electrode. Example 1: Carbon dioxide is electrolyzed using an external voltage. The performance is as follows: Figure 4 As shown. Between 600 and 825 o C, the current density (I) of the battery at 1.5V for electrolysis of carbon dioxide is shown in Table 2 below:
[0102]
[0103] From the above test results, it is known that the solid oxide cell with catalytic activity in the isolation layer exhibits good fuel cell performance in a pure hydrogen atmosphere.
[0104] Test Example 3
[0105] Example 1: The fuel electrode is fed with a hydrogen-carbon dioxide mixture (H2 / CO2=80 / 20), and the oxygen electrode is fed with air. The performance is as follows: Figure 5 When the voltage is less than the open circuit voltage, the battery operates in fuel cell mode; when the voltage is greater than the open circuit voltage, the battery operates in electrolytic cell mode. At 600-825 °C, the current of the battery at 0.5 V for power generation and 1.6 V for electrolysis is shown in Table 3 below:
[0106]
[0107] From the above test results, it is known that in a hydrogen-carbon dioxide mixture, the solid oxide cell with a catalytic activity of the isolation layer can be operated in a fuel cell or electrolyzer mode by setting a voltage, and exhibits good performance in both modes.
[0108] Test Example 4
[0109] Example 1: The fuel electrode is fed with a mixture of hydrogen and carbon dioxide in different proportions, and the oxygen electrode is fed with air. The operating temperature is 750 o C, performance as Figure 6 As shown in Table 4, the current of the battery at 0.5 V for power generation and 1.6 V for electrolysis at different hydrogen-carbon dioxide ratios is shown in Table 4:
[0110]
[0111] From the above test results, it can be seen that the solid oxide battery prepared in Example 1 exhibits good battery performance and electrolysis performance under different content atmospheres. The addition of hydrogen can improve the battery's performance in electrolyzing carbon dioxide.
[0112] The solid oxide battery with catalytic activity of the isolation layer of Example 1 is at a voltage of 1.6V and 750 o C, long-term stable operation in 80% H2-20% CO2 atmosphere, such as Figure 7 shown.
[0113] Test Example 5
[0114] Example 2: Hydrogen is introduced into the fuel electrode and air is introduced into the oxygen electrode. Example 1 is used as a fuel cell to generate electricity. The performance is as follows: Figure 8 As shown. Between 600 and 825 o The maximum power density (P) of C is shown in Table 5 below:
[0115]
[0116] From the above test results, it is known that the fuel cell performance of the solid oxide cell with catalytic activity in the isolation layer in a pure hydrogen atmosphere increases with the increase of the catalyst content in the isolation layer.
[0117] Test Example 6
[0118] Example 2: The fuel electrode is fed with a hydrogen-carbon dioxide mixture (H2 / CO2=80 / 20), and the oxygen electrode is fed with air. The performance is as follows: Fig. 9 When the voltage is less than the open circuit voltage, the battery operates in fuel cell mode; when the voltage is greater than the open circuit voltage, the battery operates in electrolytic cell mode. At 600-825°C, the current of the battery at 0.5 V for power generation and 1.5 V for electrolysis is shown in Table 6 below:
[0119]
[0120] From the above test results, it is known that in a hydrogen-carbon dioxide mixture, the performance of a solid oxide cell having a catalytically active isolation layer operating in a fuel cell or electrolyzer mode increases with the increase of the catalyst content in the isolation layer.
[0121] Test Example 7
[0122] Fig.18 The results of the comparison of Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 as hydrogen fuel cells at 600-825 oThe data of Example 1, Example 2 and Comparative Example 1 show that the output power density of the fuel cell increases with the increase of the catalyst content in the isolation layer. The data of Comparative Examples 3 and 4 show that the performance of the fuel cell can be improved by impregnating the catalyst in the first isolation layer (in contact with the oxygen electrode) and the second isolation layer (in contact with the fuel cell). Among them, the performance improvement effect of impregnating the catalyst in the double isolation layer is the most significant, followed by impregnating the catalyst in the second isolation layer.
[0123] Test Case 8
[0124] Fig.19 The figure is a comparison chart of the battery performance of Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 in a hydrogen-carbon dioxide mixed gas. The data of Example 1, Example 2 and Comparative Example 1 show that the performance of the battery in the electrolysis mode is improved as the catalyst content in the isolation layer increases. The data of Comparative Examples 3 and 4 show that the performance of the battery in the electrolysis mode can be improved when the catalyst is impregnated in the first isolation layer (in contact with the oxygen electrode) and the second isolation layer (in contact with the fuel cell).
Claims
1. A solid oxide battery having a catalytically active isolation layer, characterized in that: The invention comprises a fuel electrode, a first catalytic isolation layer, an electrolyte, a second catalytic isolation layer, and an oxygen electrode which are stacked in sequence; the fuel electrode is a perovskite-type La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3; the electrolyte is YSZ; the oxygen electrode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3; the catalytic isolation layer includes a cerium oxide-based ion conductor and a catalyst; the fuel electrode raw material includes La with a particle size of 10-40 μm 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 powder; the catalyst of the catalytic isolation layer includes Ce 0.95 Co 0.05 O 2-x 、Ce 0.95 Ru 0.05 O 2-x 、Ce 0.95 Ni 0.05 O 2-x At least one of .
2. The solid oxide battery according to claim 1, characterized in that The cerium oxide-based ion conductor of the catalytic separation layer includes Ce 0.9 G 0.1 O 1.95 、Ce 0.9 Sm 0.1 O 1.95 and Ce 0.9 La 0.1 O 1.95 At least one of .
3. A method for preparing a solid oxide battery having a catalytically active isolation layer, characterized in that: The steps include: (1) preparing a cerium oxide-based ion conductor powder into a slurry, printing it on both sides of a YSZ electrolyte substrate, and performing a first calcination to obtain a first isolation layer and a second isolation layer having a porous structure; (2) preparing a catalyst precursor into a solution and impregnating the solution into the pores of the isolation layer, followed by a second calcination to convert the precursor into a nanocatalyst in the pores of the isolation layer, thereby obtaining a first catalytic isolation layer and a second catalytic isolation layer; The impregnation process is carried out under negative pressure; (3) La 0.6 Ca 0.4 Fe 0.9 Ru 0.1 O3 powder and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 powder is prepared into fuel electrode slurry and oxygen electrode slurry, and printed on the surface of the first isolation layer and the surface of the second isolation layer, followed by a third calcination to simultaneously prepare the fuel electrode and the oxygen electrode, ensuring that the nanocatalyst structure and components in the isolation layer are stable, and finally obtaining a solid oxide battery with catalytic activity in the isolation layer; The catalyst includes Ce 0.95 Co 0.05 O 2-x 、Ce 0.95 Ru 0.05 O 2-x 、Ce 0.95 Ni 0.05 O 2-x At least one of .
4. The preparation method according to claim 3, characterized in that: In step (1), the temperature of the first calcination is 550-1050° C., and / or the time of the first calcination is 0.5-5 h.
5. The preparation method according to claim 3, characterized in that: In step (2), the catalyst precursor is at least one of the nitrate, acetate and chloride of the catalyst metal element, which is dissolved in deionized water to prepare a catalyst precursor solution, and the solution concentration is 0.5-5 mol / L.
6. The preparation method according to claim 3, characterized in that: In step (2), the temperature of the second calcination is 700-1100° C., and / or the time of the second calcination is 0.5-5 h.
7. The preparation method according to claim 3, characterized in that: In step (3), the temperature of the third calcination is 800-1200° C., and / or the time of the second calcination is 0.5-5 h.
8. Use of the solid oxide cell having a catalytically active isolation layer as claimed in any one of claims 1 to 2 in a fuel cell or an electrolytic cell.
Citation Information
Patent Citations
Medium-high temperature solid oxide ceramic oxygen pump
CN115893322A
Symmetrical solid oxide battery, preparation method and application thereof, battery operation system and construction method thereof
CN118888773A